Soybean oil transesterification by the use of a microwave flow system - Encinar, J. (2013)
The production of methyl esters from soybean transesterification by the use of a microwave flow system has been investigated. A household microwave was modified as a biodiesel reactor for continuous transesterification. The effects of temperature at the exit point (50–110 °C), the methanol/oil molar ratio (3:1, 6:1, 9:1 and 12:1) and the catalyst concentration (0.5%, 1.0% and 1.5% in weight of KOH) were evaluated. Final temperature depended on the reaction time, on the microwave power and on the reaction composition, mainly the methanol content. The obtained conversion was over 99% of methyl ester content, with a methanol/oil molar ratio of 12:1, a catalyst concentration of 1.0 wt.% and a final temperature of 70 °C (this temperature was arisen with 2 min residence time and 200 W of power). In order to compare, the conventional heating systems were also employed in transesterification in homogeneous batch and flow processes. The transesterification reaction under microwave radiation yielded similar results but with very fast heating rates.